HUBUNGAN PENGHARGAAN INTRINSIK TERHADAP MOTIVASI KERJA - Evi Maria (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2010)
People work for many reasons, and one of them is earning money. But in fact, earning moneyis not the only reason for this people to stay and work in that company. Based on the research, it’sfound that many factors can influence the working motivation of the people. This article explainsabout intrinsic rewards which influence the working motivation of the workers in a company. Theresult of this research can be used for giving recommendation for the company in how to give anappropriate reward for their workers.Keywords: work motivation, intrinsic rewards.